Associations between improvement in genitourinary symptoms of menopause and changes in the vaginal ecosystem. Issue 5 (May 2018) - Mitchell, Caroline M.; Srinivasan, Sujatha; Plantinga, Anna; Wu, Michael C.; Reed, Susan D.; Guthrie, Katherine A.; LaCroix, Andrea Z.; Fiedler, Tina; Munch, Matthew; Liu, Congzhou; Hoffman, Noah G.; Blair, Ian A.; et al.
Abstract: Objective: The aim of the study was to identify associations between improvement in genitourinary symptoms of menopause (GSM) and vaginal microbiota, vaginal glycogen, and serum estrogen. Methods: Thirty postmenopausal women enrolled in a hot flash treatment trial (oral estradiol vs venlafaxine vs placebo) who reported GSM and provided vaginal swabs at 0, 4, and 8 weeks were studied. Bacterial communities were characterized using deep sequencing targeting the 16S rRNA gene V3-V4 region. Participants selected a most bothersome genitourinary symptom (dryness, discharge, pain, itch/burn, or inability to have sex) and rated severity on a 10-point scale at baseline and 8 weeks. Vaginal glycogen and serum estradiol and estrone were measured at enrollment and 8 weeks. Comparisons according to improvement in most bothersome symptom (MBS) were made using χ 2, Wilcoxon signed-rank test, or Hotelling's t test. Results: Of 30 participants, 21 (70%) had improvement in MBS over the 8-week study and 9 (30%) had no improvement or worsening of MBS. A higher proportion of women receiving estradiol or venlafaxine reported improvement in MBS (88%, 78%) compared with placebo (54%; P  = 0.28). MBS improvement was associated with Lactobacillus- dominant vaginal microbiota at enrollment (57% vs 22%, P  = 0.08). Vaginal glycogen, serum estradiol, and estrone significantly increased in women whose MBS improved. Conclusions: A larger proportion of women whose MBS improved had a Lactobacillus dominant microbiota at enrollment than those who had no improvement during the trial, though this difference was not statistically significant. Larger trials are needed to determine whether vaginal microbiota modify or mediate treatment responses in women with GSM.